Carbon nanotube hollow sphere and preparation method thereof
Carbon nanotube hollow spheres were prepared by fluidization treatment and carbon source gas deposition treatment combined with pickling and freezing vacuum drying steps, which solved the problems of high preparation costs and complex processes in the prior art, and achieved low-cost, simple process preparation of carbon nanotube hollow spheres, which were suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411581232.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the method of preparing carbon nanotube hollow balls is costly and complex, making it difficult to achieve large-scale industrial production.
The spherical catalyst template was formed by fluidizing the catalyst powder, and the carbon nanotubes were grown by deposition and treatment with carbon source gas. The carbon nanotube hollow spheres were prepared in combination with pickling and freezing vacuum drying steps.
It has achieved low cost, simple and easy to operate in the preparation of carbon nanotube hollow balls, good controllability, and is suitable for large-scale industrial production.
Smart Images

Figure CN119591091A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of carbon nanotubes, and in particular, to carbon nanotube hollow spheres and a preparation method thereof. Background Art
[0002] Carbon nanotubes are a new type of carbon structure first discovered by Iijima, an electron microscope expert at NEC Corporation of Japan in 1991. They are seamless hollow tubes formed by curling single or multiple concentric graphite sheets, with a length of several microns to tens of microns and a diameter of 4nm-30nm. According to the size of their nanometer-scale diameter, they are called carbon nanotubes (CNTs for short). Carbon nanotubes are divided into multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs). The former is formed by the convolution of multiple layers of graphene sheets, and the latter is formed by the convolution of single-layer graphite sheets. Due to the small diameter and large aspect ratio of carbon nanotubes, they can be regarded as quasi-one-dimensional nanomaterials. Carbon nanotubes have unique structural characteristics and exhibit unique mechanical, electrical and magnetic properties. Therefore, they are widely used in many fields such as nanoelectronic devices, energy storage, field emission and flat panel displays, electrical conduction and electromagnetic shielding, and structural enhancement. Summary of the invention
[0003] In the first aspect of the present application, the present application proposes a method for preparing hollow carbon nanotube spheres, comprising: fluidizing a catalyst powder to obtain a spherical catalyst template, wherein the catalyst powder comprises nanoparticles containing a Group VIII element; depositing the spherical catalyst template, wherein the gas used in the deposition process comprises a carbon source gas, to obtain a spherical carbon nanotube catalyst complex; acid-washing the spherical carbon nanotube catalyst complex and freeze-vacuum drying the spherical carbon nanotube catalyst complex to obtain the hollow carbon nanotube spheres. The catalyst template formed by the catalyst powder is used as a support to deposit and grow carbon nanotubes thereon to control the morphology of the carbon nanotubes. The preparation method has low cost, simple and easy-to-operate process, strong controllability, and is easy to mass-produce on an industrial scale.
[0004] In some embodiments, the fluidization treatment is carried out in a fluidized bed. Therefore, the present application uses a fluidized bed reactor to achieve the construction of the catalyst template.
[0005] In some embodiments, the inner diameter of the fluidized bed is 10 mm to 100 mm, thereby facilitating the generation of catalyst templates of appropriate size, thereby controlling the size and morphology of the carbon nanotubes.
[0006] In some embodiments, the temperature of the freeze-vacuum drying is -10°C to -196°C, and the vacuum degree of the freeze-vacuum drying is less than or equal to 5Pa.
[0007] In some embodiments, the gas source of the fluidized treatment includes nitrogen and an inert gas, which is beneficial to the stable formation and deposition process of the catalyst template.
[0008] In some embodiments, the gas source introduction speed of the fluidized treatment is 0.04 m / s-0.08 m / s. Within the gas source introduction speed range of the fluidized treatment, a catalyst template with suitable size and shape can be formed.
[0009] In some embodiments, the ratio of the bed height to the inner diameter of the fluidized bed is (0.5-5): 1. The bed height of the fluidized bed, i.e., the bed height of the material added into the reactor under static conditions, within the aforementioned range of the ratio of the bed height to the inner diameter of the fluidized bed, the fluidized state in the fluidized bed is conducive to the preparation of hollow carbon nanotube spheres.
[0010] In some embodiments, the catalyst powder further includes a catalyst carrier and a loaded catalyst, wherein the catalyst powder is loaded on the catalyst carrier, and the catalyst carrier includes at least one of magnesium metal oxide, aluminum metal oxide, and dihydroxy composite metal oxide. The aforementioned catalyst carrier can accommodate nanoparticles with catalytic ability and provide a structure to support the formation of carbon nanotubes; the loaded catalyst includes at least one of single-walled carbon nanotube catalyst, double-walled carbon nanotube catalyst, few-walled carbon nanotube catalyst, multi-walled carbon nanotube catalyst, agglomerated carbon nanotube catalyst, and arrayed carbon nanotube catalyst.
[0011] In some embodiments, the bulk density of the catalyst powder is 0.03 g / cm 3 -0.6g / cm 3 When the bulk density of the catalyst powder is within the aforementioned range, it is helpful to form a catalyst template with appropriate size and density in the fluidized bed.
[0012] In some embodiments, the carbon source gas includes at least one of methane, ethane, ethylene, propane, and propylene. Thus, the carbon source gas is subjected to a deposition process to form a spherical carbon nanotube catalyst complex.
[0013] In some embodiments, the reaction temperature of the deposition process is 650°C-1200°C.
[0014] In some embodiments, the concentration of the carbon source gas is 3%-30% of the total gas flow.
[0015] In some embodiments, the pickling solution includes at least one of sulfuric acid, hydrochloric acid, and nitric acid, and the mass fraction of the pickling solution is 5%-40%. The pickling treatment can remove the catalyst template, which helps to obtain carbon nanotube hollow spheres with higher purity.
[0016] In some embodiments, before the deposition process, the method further includes: annealing the spherical catalyst template in a reducing gas atmosphere. Thus, reprocessing the catalyst template helps to make its particles more uniform.
[0017] In some embodiments, before the acid washing, the process further includes: subjecting the spherical carbon nanotube catalyst complex to oxidation treatment in an oxidizing gas atmosphere, thereby further arranging the spherical carbon nanotube catalyst complex through oxidation treatment to remove other impurities in the spherical carbon nanotube catalyst complex.
[0018] In some embodiments, the reducing gas includes at least one of hydrogen and carbon monoxide.
[0019] In some embodiments, the annealing treatment is performed at a temperature of 600°C-1000°C.
[0020] In some embodiments, the oxidizing gas includes at least one of water vapor and carbon dioxide.
[0021] In the second aspect of the present application, the present application proposes a carbon nanotube hollow sphere, wherein the specific surface area of the carbon nanotube hollow sphere is 600m 2 / g-1400m 2 / g. The carbon nanotube hollow sphere proposed in the present application has a hollow inner cavity, which can provide more accommodation space when used as a catalyst carrier, and has a wider range of uses and better use effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0023] Figure 1 The spherical carbon nanotube catalyst complex prepared in Example 1 of the present application;
[0024] Figure 2 The carbon nanotube hydrogel ball in Example 1 of the present application;
[0025] Figure 3 This is a SEM image of the appearance of the carbon nanotube hollow sphere obtained in Example 1 of the present application;
[0026] Figure 4 This is a SEM image of the interior of the carbon nanotube hollow sphere obtained in Example 1 of the present application;
[0027] Figure 5 This is a SEM image of the outer wall cross section of the carbon nanotube hollow sphere obtained in Example 1 of the present application;
[0028] Figure 6This is a SEM image of the appearance of the carbon nanotube hollow sphere obtained in Example 3 of the present application;
[0029] Figure 7 This is a high-magnification SEM image of the surface of the carbon nanotube hollow sphere obtained in Example 6 of the present application;
[0030] Figure 8 This is a SEM image of the appearance of the carbon nanotube hollow sphere obtained in Example 6 of the present application;
[0031] Fig. 9 This is a cross-sectional SEM image of the carbon nanotube hollow sphere obtained in Example 11 of the present application;
[0032] Fig.10 This is a flow chart of preparing hollow carbon nanotube spheres in one embodiment of the present application. DETAILED DESCRIPTION
[0033] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0034] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0035] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0036] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0040] The carbon nanotube hollow sphere is a sphere formed by a large number of carbon nanotubes wrapped into a sphere, with a hollow cavity inside. It can encapsulate other nanomaterials and other properties, and has potential application value in energy storage, catalyst carriers, biomedicine and other fields. For example, in the field of energy storage, the hollow sphere structure of the carbon nanotube hollow sphere can be used to prepare the negative electrode material of lithium-ion batteries. The carbon nanotube material itself has good conductivity and structural stability, while the hollow structure of the carbon nanotube hollow sphere can provide a larger internal space, and has the same specific surface area according to the type of carbon nanotube selected, which is conducive to the embedding and de-embedding of lithium ions. In addition, the hollow cavity of the carbon nanotube hollow sphere can also encapsulate other active materials to form a composite structure, further improving the energy density of the battery. In the field of catalysts, the structure of the carbon nanotube hollow sphere can be used as an efficient catalyst carrier. The cavity of the carbon nanotube hollow sphere can be used to encapsulate metal or metal oxide nanoparticles to form a core-shell structure. The carbon nanotube material can provide a good electron transfer channel to promote the catalytic reaction. At the same time, the high specific surface area of the carbon nanotube hollow sphere is also conducive to improving the utilization rate of the catalyst. In the field of biomedicine, the hollow sphere structure of carbon nanotube hollow spheres can be used as drug carriers and bioimaging probes. The cavity of the carbon nanotube hollow sphere can encapsulate drug molecules and achieve targeted delivery through functionalized carbon nanotubes.
[0041] The preparation process of carbon nanotube hollow spheres is relatively complicated. The preparation cost of carbon nanotube hollow spheres using finished carbon nanotubes is too high and cannot meet the needs of mass production. This application proposes a method for preparing carbon nanotube hollow spheres. The carbon nanotube hollow spheres are produced by carbon source gas. The process is simple and controllable, and has the prospect of industrial application.
[0042] In a first aspect of the present application, a method for preparing hollow carbon nanotube spheres is proposed. Specifically, catalyst powder is firstly processed into a catalyst template having a spherical structure by fluidization treatment in a fluidized bed.
[0043] Then, the carbon nanotubes are grown in situ in the gaps inside and outside the catalyst template through deposition treatment to form the internal support skeleton of the hollow carbon nanotube sphere. Figure 1 , to obtain a spherical carbon nanotube catalyst complex. The catalyst template is then removed by inorganic acid and washed with deionized water. Figure 2, carbon nanotube hydrogel balls can be obtained. Nanoparticles with the function of catalyzing the growth of carbon nanotubes are loaded on catalyst carriers to achieve spatial dispersion and spatial distribution control, thereby obtaining catalyst powder. Nanoparticles are contained between the interlayer gaps of the catalyst microscopic layered structure. With the assistance of the nanoparticles with catalytic function, the carbon source gas distributes carbon elements along the nanoparticles and deposits to form carbon nanotubes. The catalyst powder forms a catalyst spherical template. When the catalyst catalyzes the carbon source gas, the spatial position where the carbon element is deposited will be affected by the morphology of the spherical template. The carbon element is deposited along the surface and internal gaps of the spherical catalyst template to form a spherical carbon nanotube catalyst complex. Therefore, the preparation method can form a spherical structure during the growth of carbon nanotubes, and has the advantages of low preparation cost, simple and easy operation of the process, strong controllability, and easy large-scale industrial batch production.
[0044] The method for preparing hollow carbon nanotube spheres in the present application comprises the following steps:
[0045] S100: fluidizing the catalyst powder to obtain a preliminary spherical catalyst template, wherein the catalyst powder includes nanoparticles containing a Group VIII element;
[0046] In some embodiments, the fluidization treatment is performed in a fluidized bed. The fluidized bed can be a fluidized bed granulator or other equipment that can achieve fluidization in the bed layer, but is not limited to the listed equipment. Other equipment not listed in the same scope of the principle is also applicable. Catalyst powder agglomeration is achieved through the fluidized bed to form a catalyst template.
[0047] In some embodiments, the inner diameter of the fluidized bed is 10 mm-100 mm.
[0048] By controlling the inner diameter of the reactor, the size and morphology of the formed catalyst template can be regulated, thereby controlling the preparation of a catalyst template with a suitable size.
[0049] As an example, the inner diameter of the fluidized bed may be 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, or 100 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some embodiments, the inner diameter of the fluidized bed may be 50 mm.
[0051] In some embodiments, the temperature of the freeze-vacuum drying is -10°C to -196°C, and the vacuum degree of the freeze-vacuum drying is less than or equal to 5Pa.
[0052] In some embodiments, the gas source for the fluidization process includes nitrogen and an inert gas.
[0053] The gas of the gas source can be nitrogen or an inert gas. The chemical and physical properties of the aforementioned gas are stable, which can reduce the occurrence of side reactions and is conducive to the stable formation of the catalyst template and the deposition process.
[0054] In some embodiments, the source gas may be at least one of nitrogen, helium, and argon.
[0055] In some embodiments, the gas source introduction speed of the fluidization process is 0.04m / s-0.08m / s.
[0056] During the fluidization process driven by the gas source flow, the catalyst powder produces a boundary effect with the reactor tube wall. A certain degree of boundary effect is conducive to the catalyst powder forming a catalyst template. At the same time, because the catalyst powder itself has adhesion, during the fluidization process, the catalyst powders collide with each other and agglomerate into a sphere to form a catalyst template. Within the gas source introduction speed range of the aforementioned fluidization process, it is helpful to form a catalyst template with a suitable size and shape.
[0057] As an example, the gas source introduction speed of the fluidization treatment may be 0.04m / s, 0.045m / s, 0.05m / s, 0.055m / s, 0.06m / s, 0.065m / s, 0.07m / s, 0.075m / s, 0.08m / s, 0.085m / s, etc., but is not limited to the listed values.
[0058] In some embodiments, the gas source introduction speed of the fluidization process may be 0.045 m / s.
[0059] In some embodiments, the ratio of the bed height to the inner diameter of the fluidized bed may be (0.5-5): 1. The bed height of the fluidized bed, i.e., the bed height of the material added to the reactor under static conditions, can effectively form spherical carbon nanotube catalyst complexes within the aforementioned range of the ratio of the bed height to the inner diameter of the fluidized bed.
[0060] As an example, the ratio of the bed height to the inner diameter of the fluidized bed may be 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some embodiments, the ratio of the bed height to the inner diameter of the fluidized bed may be 2:1.
[0062] In some embodiments, the catalyst powder further includes a catalyst carrier and a loaded catalyst, the catalyst powder is loaded on the catalyst carrier, the catalyst carrier includes at least one of magnesium metal oxide, aluminum metal oxide, and dihydroxy composite metal oxide; the loaded catalyst includes at least one of single-walled carbon nanotube catalyst, double-walled carbon nanotube catalyst, few-walled carbon nanotube catalyst, multi-walled carbon nanotube catalyst, clustered carbon nanotube catalyst, and arrayed carbon nanotube catalyst.
[0063] The catalyst carrier in the catalyst powder can be magnesium oxide, spinel, vermiculite, hydrotalcite, etc. The catalyst carrier has a layered structure, and the gaps between its layers can be used as spaces to accommodate catalysts and support the generation of carbon nanotubes, and can carry different types of carbon nanotube catalysts, which can be single-walled carbon nanotube catalysts, double-walled carbon nanotube catalysts, few-walled carbon nanotube catalysts, multi-walled carbon nanotube catalysts, arrayed carbon nanotube catalysts, agglomerated carbon nanotube catalysts, etc., to form a porous morphology on the surface of the nanotube hollow sphere, so that the nanotube hollow sphere can have a gel structure.
[0064] In some embodiments, the bulk density of the catalyst powder may be 0.03 g / cm 3 -0.6g / cm 3 .
[0065] When the bulk density of the catalyst powder is within the above range, during the fluidization process, the catalyst powder can form a part of the bubble phase and a part of the emulsion phase in the fluidized bed, so that they can collide with each other to a certain extent to agglomerate into a spherical shape. By controlling the bulk density of the catalyst powder and the inner diameter of the reactor, it is helpful to control the formation of a catalyst template with a suitable size, density and morphology.
[0066] As an example, the bulk density of the catalyst powder may be 0.03 g / cm 3 , 0.04g / cm 3 , 0.05g / cm 3 , 0.1g / cm 3 , 0.2g / cm 3 , 0.3g / cm 3 , 0.4g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 The above values are not limited to the above values, and other values not listed in the above values are also applicable.
[0067] In some embodiments, the bulk density of the catalyst powder may be 0.22 g / cm 3 .
[0068] In some embodiments, before the deposition process, the method further includes: annealing the spherical catalyst template in a reducing gas atmosphere.
[0069] By increasing the temperature to anneal the catalyst template, a pinning effect can be generated on the surface of the catalyst template powder particles, thereby further controlling the formation of spherical particles through fluidization. In addition, annealing can remove impurities on the surface of the catalyst template, reduce the structural defects of the catalyst template, and achieve reprocessing of the catalyst template size, which helps to obtain a catalyst template with more uniform particle size.
[0070] In some embodiments, the reducing gas includes at least one of hydrogen and carbon monoxide.
[0071] In some embodiments, the annealing process may be performed at a temperature of 600° C.-1000° C.
[0072] As an example, the temperature condition of the annealing process may be 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., or 950° C., etc.
[0073] S200: performing a deposition process on the spherical catalyst template, wherein the gas used in the deposition process includes a carbon source gas, so as to obtain a spherical carbon nanotube catalyst complex;
[0074] In some embodiments, the carbon source gas includes at least one of methane, ethane, ethylene, propane, and propylene. Thus, the carbon source gas undergoes chemical vapor deposition on the catalyst template to form a spherical carbon nanotube catalyst complex.
[0075] In some embodiments, the diameter of the spherical carbon nanotube-catalyst composite formed by combining the spherical carbon nanotubes and the catalyst is about 800 μm.
[0076] In some embodiments, the diameter of the spherical carbon nanotube catalyst complex may be 400 μm-2000 μm. The diameter of the spherical carbon nanotube catalyst complex is affected by the density of the catalyst template, the morphology of the catalyst template, the inner diameter of the reactor, and the like.
[0077] In some embodiments, the reaction temperature of the deposition process is 650°C-1200°C.
[0078] In some embodiments, the carbon source gas flow rate accounts for 3%-30% of the total gas flow rate. Thus, the total gas includes the carbon source gas and the gas of the fluidized gas process.
[0079] As an example, the ratio of the carbon source gas flow to the total gas flow may be 3%, 5%, 8%, 10%, 12%, 15%, 17%, 20%, 23%, 25%, 28%, 30%, etc.
[0080] S300: performing acid washing treatment on the spherical carbon nanotube catalyst complex and freeze-vacuum drying to obtain the carbon nanotube hollow sphere.
[0081] Thus, after the spherical carbon nanotube catalyst complex is subjected to an acid-washing treatment, the obtained carbon nano hollow spheres include free water, forming carbon nanotube hydrogel spheres. After the carbon nanotube hydrogel spheres are freeze-dried, the water contained in the carbon nanotube hydrogel spheres freezes under the low temperature state of the freeze-drying treatment. Subsequently, under vacuum conditions, the ice crystals in the carbon nanotube hydrogel spheres sublimate into water vapor, and the negative pressure force generated by the vacuum environment forces the water vapor in the carbon nanotube spheres to move outward and drive the carbon nanotubes in the center of the carbon nanotube spheres, referring to Figure 3 , forming a cavity structure inside the carbon nanotube hollow sphere, and the outer wall is a porous structure of the carbon nanotube, thus forming a carbon nanotube hollow sphere with a stable structure.
[0082] In some embodiments, the hollow carbon nanotube sphere can be a sphere, a cocoon-shaped body, or other irregular shapes that are approximately spherical.
[0083] In some embodiments, the carbon nanotube hollow sphere has a carbon tube length of 1 μm-300 μm.
[0084] In some embodiments, the temperature of the freeze-vacuum drying process may be less than or equal to -10°C, and the vacuum degree of the freeze-vacuum drying process may be less than or equal to 5Pa.
[0085] In some embodiments, the freeze-vacuum drying process may be performed for a period of time greater than or equal to 12 hours.
[0086] In some embodiments, the freeze-vacuum drying process may be performed using a freeze-vacuum dryer.
[0087] In some embodiments, the pickling solution includes at least one of sulfuric acid, hydrochloric acid, and nitric acid, and the mass concentration of the pickling solution may be 5%-40%.
[0088] The spherical carbon nanotube catalyst complex can be assisted by continuous slow stirring in the acid-washing solution to dissolve the catalyst carrier and fully remove the catalyst template. The catalyst template is dissolved in the acid-washing solution to obtain a carbon nanotube hollow sphere with higher purity and larger specific surface area.
[0089] In some embodiments, the stirring speed of the pickling treatment may be 30 rpm-60 rpm.
[0090] In some embodiments, the method further comprises: washing the carbon nanotube hollow spheres after the acid washing with deionized water for more than or equal to 3 times, and adjusting the pH value of the carbon nanotube hollow spheres to 6-8.
[0091] In some embodiments, the acid-washed hollow nanotube spheres may contain water, and the mass fraction of carbon nanotubes in the water-containing hollow nanotube spheres is 1%-4%.
[0092] In some embodiments, reference Fig.10 Before the acid washing treatment, the method further includes: performing an oxidation treatment on the spherical carbon nanotube catalyst complex in an oxidizing gas atmosphere.
[0093] The carbon source gas is introduced into the fluidized bed to cause chemical vapor deposition, and the carbon nanotube structure begins to grow. Amorphous carbon is also generated while the carbon nanotube structure is generated. The generated amorphous carbon can be removed by introducing an oxidizing gas for oxidation treatment, and the structure of the carbon nanotube is further arranged.
[0094] In some embodiments, the mass fraction of carbon nanotubes in the oxidized spherical carbon nanotube catalyst composite is 1%-50%.
[0095] In some embodiments, the mass fraction of carbon nanotubes in the oxidized spherical carbon nanotube catalyst composite is about 20%.
[0096] The content of carbon nanotubes in the spherical carbon nanotube catalyst complex is affected by the type of catalyst and the type of carbon source.
[0097] In some embodiments, the oxidizing gas includes at least one of water vapor and carbon dioxide.
[0098] In the second aspect of the present application, the present application proposes a carbon nanotube hollow sphere, wherein the specific surface area of the carbon nanotube hollow sphere is 600m 2 / g-1400m 2 / g.
[0099] The carbon nanotube hollow spheres proposed in the present application have a larger specific surface area, which can provide more accommodation space as a catalyst carrier, and have a wider range of uses and better use effects.
[0100] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0101] Example 1
[0102] S1: Single-walled carbon nanotube catalyst powder with Fe nanoparticles loaded on MgO was used. The catalyst powder with a bed diameter ratio of 1.5 was placed in a reactor for fluidization treatment. The bulk density was 0.24 g / cm 3 , the inner diameter of the reactor is 50 mm to obtain a spherical catalyst template
[0103] S2: Using methane as the carbon source gas, the gas velocity is 0.045 m / s, the fluidized bed is used as the reactor, and the temperature is 900°C to prepare the spherical carbon nanotube catalyst complex by vapor deposition method
[0104] S3: Using CO2 to oxidize the prepared spherical carbon nanotube catalyst complex
[0105] S4: The spherical carbon nanotube catalyst complex is acid-washed with a 25wt% sulfuric acid solution, the mass ratio of the acid solution to the catalyst powder is 10:1, the temperature is 80°C, the time is 8h, and the stirring speed is 50rpm
[0106] S5: washing with deionized water and adjusting the pH value of the carbon nanotube hollow spheres to 6-7 to obtain carbon nanotube-containing hydrogel spheres;
[0107] S6: The carbon nanotube hydrogel balls are placed in a cold trap and frozen for 8 hours, the temperature of the cold trap is minus 40°C; then they are placed in a vacuum dryer for vacuum drying, the vacuum degree of the vacuum dryer is 3 Pa, and the vacuum drying time is 24 hours.
[0108] Figure 1-2 They are the spherical carbon nanotube and catalyst complex and the carbon nanotube hydrogel ball of this embodiment. Figure 1-2 It can be seen that the carbon nanotube hollow spheres still maintain a complete spherical structure after being treated with inorganic acid to remove the catalyst template. Figure 3-5 The following are the SEM images of the appearance of the carbon nanotube hollow sphere prepared in this example, the SEM images of the interior of the carbon nanotube hollow sphere, and the SEM images of the cross-section of the outer wall of the carbon nanotube hollow sphere. Figure 3-5It can be seen that the diameter of the carbon nanotube hollow sphere is about 1000 μm, the surface has a porous structure, the interior is a hollow structure, and the outer wall is a multi-layer carbon nanotube oriented stacking structure with an outer wall thickness of less than 10 μm.
[0109] Example 2
[0110] Example 2 is consistent with Example 1, except that the bulk density of the catalyst powder is 0.44 g / cm 3 .
[0111] The test results show that when the catalyst stacking density is increased, the size of the obtained carbon nanotube hollow spheres decreases under the condition that the inner diameter and gas velocity of the reactor remain unchanged.
[0112] Example 3
[0113] Example 3 is consistent with Example 1, except that the bulk density of the catalyst powder is 0.33 g / cm 3 , bed diameter ratio is 6.
[0114] Figure 6 The SEM image of the hollow carbon nanotube sphere prepared in this example is shown in FIG. Figure 6 and Figure 3 By comparison, it can be seen that when the catalyst stacking density is increased, the size of the obtained carbon nanotube hollow spheres decreases under the condition that the inner diameter and gas velocity of the reactor remain unchanged.
[0115] Example 4
[0116] Example 4 is consistent with Example 1, except that the inner diameter of the reactor is 100 mm and the bed diameter ratio is 3.
[0117] The test results show that the size of the spherical carbon nanotube catalyst complex formed by the prepared carbon nanotubes and catalysts decreases as the reactor diameter increases. In the MgO catalyst system, the size of the prepared carbon nanotube hollow spheres is inversely proportional to its packing density and the inner diameter of the reactor.
[0118] Example 5
[0119] Example 5 is consistent with Example 1, except that the carbon source gas is 20% propylene and 80% methane.
[0120] The test results show that mixed carbon sources can still be used to prepare carbon nanotube hollow spheres.
[0121] Example 6
[0122] Example 6 is consistent with S3-S5 of Example 1, except that:
[0123] S1: Fe nanoparticles were loaded on LDH (layered magnesium aluminum hydroxide) multi-walled array carbon nanotube catalyst powder. The catalyst powder with a bed diameter ratio of 4.5 was placed in a reactor for fluidization treatment. The bulk density was 0.038 g / cm 3 , the inner diameter of the reactor is 20 mm to obtain a spherical catalyst template
[0124] S2: Using ethylene as the carbon source gas, the gas velocity is 0.045 m / s, the fluidized bed is used as the reactor, and the temperature is 700 ° C, a spherical carbon nanotube catalyst complex is prepared by vapor deposition method
[0125] Figure 7 , Figure 8 The following are high-power SEM images of the surface of the carbon nanotube hollow sphere and the SEM images of the appearance of the carbon nanotube hollow sphere. Figure 7-8 It can be seen that the surface of the ball is composed of arrayed multi-walled carbon nanotubes, and the size of the carbon nanotube hollow ball prepared by using LDH as a catalyst carrier and catalyst powder as a raw material is much smaller than that of the carbon nanotube hollow ball prepared by using MgO as a catalyst carrier and catalyst powder as a raw material.
[0126] Example 7
[0127] Example 7 is consistent with Example 6, except that the bulk density is 0.07 g / cm 3 of LDH catalyst.
[0128] The test results show that the size of the prepared carbon nanotube hollow spheres decreases when the catalyst packing density is increased and the inner diameter and gas velocity of the reactor remain unchanged. Due to the different catalyst carriers, the size change of the LDH catalyst after changing the packing density is less obvious compared with the magnesium oxide carrier catalyst.
[0129] Example 8
[0130] Example 8 is consistent with Example 6, except that the inner diameter of the reactor is 50 mm and the bed diameter ratio is 2.
[0131] The test results show that the inner diameter of the reactor in this embodiment is increased, and the diameter of the prepared carbon nanotube hollow spheres is slightly smaller than that in Example 6.
[0132] Example 9
[0133] Example 9 is consistent with Example 6, except that the inner diameter of the reactor is 80 mm and the bed diameter ratio is 1.5.
[0134] The test results show that the inner diameter of the reactor in this example is greatly increased, resulting in a smaller size of the prepared carbon nanotube and catalyst composite, which is close to the powder particle size.
[0135] Example 10
[0136] Example 10 is consistent with Example 1, except that the solution for pickling treatment is a 30 wt % hydrochloric acid solution.
[0137] The test results show that hydrochloric acid can also be used as an inorganic acid to remove the catalyst template from the carbon nanotube and catalyst complex.
[0138] Embodiment 11
[0139] Example 11 is consistent with Example 1, except that the cold trap temperature is minus 20°C.
[0140] The test results show that the wall thickness of the dried carbon nanotube hollow spheres changes due to the change of temperature when vacuum drying is carried out at different temperatures. Fig. 9 This is a cross-sectional SEM image of the carbon nanotube hollow sphere prepared in this example. Fig. 9 It can be seen that the wall thickness is greater than 300 μm. The freezing temperature in this embodiment is higher than that in embodiment 1, so that the wall thickness of the carbon nanotube hollow sphere is much greater than that in embodiment 1.
[0141] Comparative Example 1
[0142] Comparative Example 1 is consistent with Example 1, except that the gas for oxidation treatment is air.
[0143] In Comparative Example 1, air is used as an oxidant for oxidation treatment to purify and remove amorphous carbon in carbon nanotubes. The oxidation reaction is an exothermic reaction, and the oxidation of amorphous carbon by air will also remove a large number of carbon nanotubes, resulting in the carbon nanotubes remaining in the spherical carbon nanotube catalyst complex formed by the carbon nanotubes and the catalyst being less than 1%, and an effective skeleton support structure cannot be formed, and thus the carbon nanotube hollow sphere cannot be formed.
[0144] Comparative Example 2
[0145] Comparative Example 2 is consistent with Example 1, except that the inner diameter of the reactor is 140 mm and the gas velocity is 0.07 m / s.
[0146] It can be seen from Comparative Example 2 that when the inner diameter of the reactor is too large, its boundary effect has little effect on the catalyst particles, which is not conducive to the catalyst forming a spherical catalyst template. When the reaction gas velocity is high, the particles of the catalyst powder collide violently and cannot form a spherical structure, resulting in the failure to form a spherical carbon nanotube catalyst complex composed of carbon nanotubes and catalysts.
[0147] In the description of the present application, “plurality” means two or more.
[0148] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0149] In the description of this application, "same chemical composition" should be understood in a broad sense, that is, the main components of the two have the same chemical composition, or the chemical composition of the two is basically the same, and may have errors within the allowable range in the field that are understandable to those skilled in the art or contain impurities within the allowable range.
[0150] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0151] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing hollow carbon nanotube spheres, characterized in that: include: Fluidizing a catalyst powder to obtain a spherical catalyst template, wherein the catalyst powder includes nanoparticles containing a Group VIII element; Performing a deposition process on the spherical catalyst template, wherein the gas used in the deposition process includes a carbon source gas, so as to obtain a spherical carbon nanotube catalyst complex; The spherical carbon nanotube catalyst complex is subjected to acid washing treatment and freeze-vacuum drying to obtain the carbon nanotube hollow sphere.
2. The method according to claim 1, characterized in that: The fluidization treatment is carried out in a fluidized bed; and / or, The inner diameter of the fluidized bed is 10 mm to 100 mm; and / or, The temperature of the freeze-vacuum drying is -10°C to -196°C, and the vacuum degree of the freeze-vacuum drying is less than or equal to 5Pa.
3. The method according to claim 2, characterized in that The gas source for the fluidization process includes nitrogen and an inert gas; and / or, The gas source introduction speed of the fluidization treatment is 0.04m / s-0.08m / s; and / or, The ratio of the bed height to the inner diameter of the fluidized bed is (0.5-5):
1.
4. The method according to claim 1, further comprising a catalyst carrier and a supported catalyst, wherein the catalyst powder is supported on the catalyst carrier, and the catalyst carrier comprises at least one of magnesium metal oxide, aluminum metal oxide, and dihydroxy composite metal oxide; The supported catalyst includes at least one of a single-walled carbon nanotube catalyst, a double-walled carbon nanotube catalyst, a few-walled carbon nanotube catalyst, a multi-walled carbon nanotube catalyst, a clustered carbon nanotube catalyst, and an arrayed carbon nanotube catalyst.
5. The method according to claim 1, characterized in that: The bulk density of the catalyst powder is 0.03 g / cm 3 -0.6g / cm 3 .
6. The method according to claim 1, characterized in that The carbon source gas includes at least one of methane, ethane, ethylene, propane and propylene; and / or, The reaction temperature of the deposition process is 650°C-1200°C; and / or, The flow rate ratio of the carbon source gas is 3%-30% of the total gas flow rate; and / or, The pickling solution includes at least one of sulfuric acid, hydrochloric acid and nitric acid, and the mass concentration of the pickling solution is 5%-40%.
7. The method according to any one of claims 1 to 6, characterized in that: Further including: Before the deposition process, the method further comprises: annealing the spherical catalyst template in a reducing gas atmosphere; and / or, Before the acid washing treatment, the method further includes: performing an oxidation treatment on the spherical carbon nanotube catalyst complex in an oxidizing gas atmosphere.
8. The method according to claim 7, characterized in that The reducing gas includes at least one of hydrogen and carbon monoxide; and / or, The temperature condition of the annealing treatment is 600°C-1000°C.
9. The method according to claim 7, characterized in that: The oxidizing gas includes at least one of water vapor and carbon dioxide.
10. A carbon nanotube hollow sphere prepared according to the method according to any one of claims 1 to 9, characterized in that: The specific surface area of the carbon nanotube hollow sphere is 600m 2 / g-1400m 2 / g.